Stock Market Returns to Financial Innovations Before and During the Financial Crisis in the United States and Europe1. Issue 5 (27th November 2013) - Schöler, Lisa; Skiera, Bernd; Tellis, Gerard J.
<x xml:space="preserve">Abstract</x> Prior studies have focused on innovations in various contexts but largely excluded financial innovations, despite their notable importance. Not surprisingly, financial innovations account for a substantial portion of world economies and the huge market capitalization of banks. Therefore, the authors focus on studying the type, success, and causes of success of financial innovations. Using an event study and financial expert ratings, this study analyzes the types of and payoffs to 428 financial innovations by 39 major banks in North America and Western Europe between 2001 and 2010. The results indicate that security and credit instruments constitute the most common and insurance innovations the least common financial innovations, which vary substantially by economic cycles and location. The average cumulative abnormal stock market returns to a financial innovation are $146 million. They are twice as high in the United States as in Western Europe. Thus, the market considers financial innovations profitable, not harmful, despite their apparent responsibility for the financial crisis. Surprisingly, the cumulative abnormal stock market returns to financial innovations are higher in recessions than in expansions. The authors find that riskiness and radicalness of the innovation increases abnormal returns, while complexity decreases cumulative abnormal stock market returns. Two interaction effects stand out: Riskiness of financial innovations has higher cumulative abnormal stock market returns in the United States than in Western Europe. Radicalness has lower cumulative abnormal stock market returns in recessions than in expansions. The authors discuss important implications of the findings.